2016
DOI: 10.1159/000452763
|View full text |Cite
|
Sign up to set email alerts
|

Leg Muscle Involvement in Facioscapulohumeral Muscular Dystrophy: Comparison between Facioscapulohumeral Muscular Dystrophy Types 1 and 2

Abstract: Background: Facioscapulohumeral muscular dystrophy (FSHD) presents with 2 genetically distinct types. We describe for the first time the MRI patterns of leg muscle involvement in type 2 and compare it with type 1. Methods: The intramuscular fat content was assessed on lower extremity axial T1-weighted MRI scans in 6 FSHD1 and 5 FSHD2 patients. Results: Overall, the muscle involvement profile did not differ substantially between FSHD1 and FSHD2. In the thigh, the dorsomedial compartment including the semimembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Involvement of lower leg muscles in patients with FSHD, especially of the GM and TA, is a typical clinical and MRI finding and has also been observed in our study [33][34][35][36]. We showed as previously reported that fatty replacement of the muscle increases with age and with disease duration and correlates inversely with muscle flexor strength [37].…”
Section: Discussionsupporting
confidence: 89%
“…Involvement of lower leg muscles in patients with FSHD, especially of the GM and TA, is a typical clinical and MRI finding and has also been observed in our study [33][34][35][36]. We showed as previously reported that fatty replacement of the muscle increases with age and with disease duration and correlates inversely with muscle flexor strength [37].…”
Section: Discussionsupporting
confidence: 89%
“…Muscle magnetic resonance imaging (MRI) has been recognized as the main tool to identify distinctive patterns of involvement in FSHD1 [13][14][15][16] and also to study disease pathophysiology [17,18] and progression [19][20][21][22]. The radiological features of FSHD2 on MRI have not been defined yet, since MRI studies had been conducted only on single patients or small cohorts [23,24]. Due to the rarity of the disease, multicentre studies are needed to collect sufficient numbers of patients to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…7 MRI demonstrates imaging changes consistent with this fatty replacement. 8 Previous cross-sectional MRI studies assessing fattyreplaced muscle show common patterns of muscle involvement across patient groups, where many FSHD affected individuals experienced fatty replacement of hamstrings, tibialis anterior and gastrocnemius muscles [9][10][11][12][13][14][15] before fatty replacement in other muscles. Despite these general similarities, within affected individuals extensive variability and significant asymmetry can be present.…”
mentioning
confidence: 99%